Extravasal albumin concentration modulates contractile responses of renal afferent arterioles. (19th August 2017) - Gao, X.; Liu, Z. Z.; Mohammed, H.; Braun, D.; Zhuge, Z.; Liu, M.; Lai, E. Y.; Jansson, L.; Carlström, M.; Patzak, A.; Persson, A. E. G.
Abstract: Aim: Afferent arterioles (AA) hold a key position in the regulation of renal blood flow and glomerular filtration rate. Being the effector site of tubuloglomerular feedback, the afferent arteriole contributes to the renal handling of sodium and fluid. Dehydration goes along with increased renal interstitial protein concentration. Here, the hypothesis was tested that extravasal protein concentration directly modulates afferent arteriolar tone, a mechanism which may contribute to body fluid volume control. Method: The effect of increased extravasal albumin concentration on the vascular reactivity was investigated in renal AA and interlobar arteries of mice, in rat renal AA and in pancreatic islet arterioles. Results: Albumin (2 and 4% in the bath solution) significantly potentiated the contractile response of renal afferent arterioles induced by angiotensin II and adenosine, as well as their combination, compared to the control situation (0.1% albumin). Albumin did not influence the contractility of larger renal vessels or pancreatic islet arterioles. Mimicking the increase in the osmolality induced by 4% albumin by applying mannitol to the bath solution also increased the response of renal arterioles to Ang II. However, the effect was smaller compared to that of albumin. The nitric oxide bioavailability, measured by DAF‐FM fluorescence, was reduced in afferent arterioles exposed to 4% albumin. Conclusion: The protein‐induced modulation of AA tone is mediated by the increased osmolality as well as by NO scavenging. The results suggest a possible contribution of these mechanisms to the control of extracellular fluid volume via adjustment of renal blood flow and glomerular filtration rate.